2015
DOI: 10.3892/mmr.2015.4388
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the expression of sphingosine 1-phosphate 2 receptors regulates the differentiation of pre-adipocytes

Abstract: Abstract. Sphingosine 1-phosphate (S1P) is a bioactive lipid mediator that regulates multiple signals through S1P receptors responsible for biological responses. In particular, the S1P 2 receptor has distinct roles in the S1P-mediated differentiation of certain cell types. The present study was the first, to the best of our knowledge, to report the role of the S1P 2 receptor in the adipocyte differentiation of 3T3-L1 pre-adipocytes. In order to investigate the influence of S1P 2 receptors in the anti-adipogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 29 publications
(54 reference statements)
0
12
1
Order By: Relevance
“…Our result that S1pr2 signal attenuated adipogenesis was consisted with that of Moon et al [10]. On the other hand, Jeong et al, despite performing the same experiment as ours to silencing S1pr2 with siRNA in 3T3-L1 adipocytes, obtained the opposite result to ours that adipogenesis was accelerated [11]. We cannot explain this discrepancy now.…”
Section: S1p and Adipocytescontrasting
confidence: 70%
“…Our result that S1pr2 signal attenuated adipogenesis was consisted with that of Moon et al [10]. On the other hand, Jeong et al, despite performing the same experiment as ours to silencing S1pr2 with siRNA in 3T3-L1 adipocytes, obtained the opposite result to ours that adipogenesis was accelerated [11]. We cannot explain this discrepancy now.…”
Section: S1p and Adipocytescontrasting
confidence: 70%
“…As mentioned previously in Modulating Ceramide Metabolism to Prevent and/or Reverse Obesity-Related Disease, it has been demonstrated that activation of SphK1 to enhance flux of ceramide into S1P may also protect against obesity-induced insulin resistance, and recent studies have also suggested that S1P may possess additional salutary actions against obesity-related metabolic dysfunction (13). These salutary actions of S1P against the obesity phenotype include inhibition of adipocyte differentiation (57,73) and promoting survival of cardiac myocytes following exposure to hypoxia (124). Hence, ceramide/sphingolipid metabolism is intricate and complex and possesses multiple nodes at which its specific metabolites/intermediates can influence various aspects of obesity-associated metabolic dysfunction.…”
Section: Caveats Future Directions and Summarymentioning
confidence: 77%
“…↑ P-ERK ↑ adipocyte proliferation [199] 3T3-F442A adipocyte VPC-23019 (10µM, 5 d) ↑ adipocyte-specific gene expression (Fabp4, Lpl, Adipoq) ↑ adipogenic differentiation [199] 3T3-L1 adipocytes siRNA S1P2 ↓ S1P-induced downregulation of PPARγ and P-JNK ↓ S1P-mediated inhibition of lipid accumulation [200] 3T3-L1 adipocytes DMS [199]…”
Section: Resultsmentioning
confidence: 99%
“…pre-adipocytes inhibits the JNK pathway and induces down-regulation of PPARγ expression [200]. S1P also increases the expression of S1P2 during the differentiation of 3T3-L1 preadipocytes and this is associated with the inhibition of adipogenesis and lipid accumulation [198].…”
Section: S1p and Adipose Tissue Remodelingmentioning
confidence: 99%